Spegazzinia cryptica sp. nov. (Didymosphaeriaceae) from the western Pacific monsoon region - Lu, Liang-Ting; Sugita, Ryosuke; Sato, Misaki; Tanaka, Kazuaki; Kirschner, Roland (Phytotaxa, 2024)
A new species of Spegazzinia on dead leaves of Cyperaceae and Poaceae from Taiwan and Japan is described and illustrated as S. cryptica. By the four to eight cells comprising the body of the α conidia, the species differs from other species of Spegazzinia. Although this fungus could hardly be distinguished from S. musae by morphology, it is revealed as a new species by diagnostic bases and phylogenetic analyses of nucrDNA and translation elongation factor 1-α gene (ITS/LSU and TEF) sequences.